Wild edible fruits as a potential source of phytochemicals with capacity to inhibit lipid peroxidation - Morales, Patricia (2013)
The edible fruits of four wild small trees or shrubs (Arbutus unedo, Crataegus monogyna, Prunus spinosa and Rubus ulmifolius) traditionally consumed in the Iberian Peninsula were studied to evaluate their potential for human nutrition, considering their content in bioactive compounds. Lipophilic phytochemicals, such as fatty acids and tocopherols, as well as some hydrophilic antioxidants, such as vitamin C (ascorbic and dehydroascorbic acids), and organic acids, were analysed. In addition, the antioxidant activity, measured as lipid peroxidation inhibition (β-carotene/linoleate and TBARS assays), was evaluated in each fruit. As far as we know, this is the first report relating to bioactive compounds in wild fruits with relation to the lipid peroxidation inhibition. Data revealed that these wild edible fruits are good sources of bioactive compounds such as ascorbic acid, tocopherols and polyunsaturated fatty acids. They could be considered as functional foods or potential sources of lipidic bioactive compounds to be included as antioxidant food ingredients or in dietary supplements, mainly Rubus ulmifolius, due to its high content in tocopherols. This study provides useful and relevant information that justify tocopherols influence in the prevention of lipid peroxidation, due to the strong correlation observed (r > 0.95) between these lipophilic bioactive compounds and the antioxidant activity.